The Politics of Street Vendors: Community Perspectives in the State in Medan City - Tengku Irmayani; Juang Solala Laiya; Ruri Prihatini Lubis (Jurnal Public Policy, 2022)
Street vendors illegally occupy urban space and conduct business there. As a result, street vendors are frequently targets of government policing and disciplinary operations (state). The people's relationship with the state includes aspects of rights and obligations. This study examines the perspectives of street vendors in Medan, North Sumatra Province, Indonesia. When it comes to rights and obligations, street vendors have their own point of view. The research on street vendors in Medan City concluded, using the survey technique and observation, that the state was not present to provide social protection guarantees, in community activities, or efforts to improve their welfare and quality of life.